(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses the problems of demography. The authors examine the concept and causes of depopulation, investigate problems of fertility, mortality, life expectancy, migration. The article also discusses the features of state regulation of demographic processes in the Republic of Kazakhstan. The authors suggest recommendations for further improvement of the state. Keywords: demography, depopulation, demographic security, the state, the function of the state.